KESETIMBANGAN ADSORPSI ISOTERMIS LOGAM Cr (VI) PADA FLY ASH - Saripah sobah; Fitria Fitria; Yano Hurung Anoi; Diana Diana; Precast Octavianus (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2021)
The Purpose of this study was to determine the optimum adsorption time of fly ash from the PT. Pupuk Kaltim in adsorbing Cr metal, optimal stirring speed, and optimal weight of fly ash under isothermic conditions in batches using the Langmuir equation has been carried out at atmospheric conditions, temperature 27oC. Fly ash varies in weight and stirring speed. The filtrate was added with 2 mL of 0.1% NH4Cl after equilibrium, then analyzed using AAS AA-7000. The optimal adsorption time of fly ash in adsorbing Cr metal is 60 minutes. The optimal adsorption weight of fly ash is in 50 mL of Cr solution is 2 grams with an average efficiency value of 91.22%. The optimum stirring speed of fly ash to adsorb Cr metal is 200 rpm. Keywords: isothermic adsorption, fly ash, Cr metal